Analysis of Students’ Ability to Apply Physics Concepts through Environmental-Based Worksheets on Junior High School - I Gede Purwana Edi Saputra; Harnipa Harnipa; Pertiwi Pertiwi; Nurhikmah Hasan (Universitas Muhammadiyah Makassar, 2022)
This research is a descriptive research with a quantitative approach that aims to determine the students’ ability to apply physics concepts in junior high school by using environmental-based worksheets. The sample of this research were 31 students of class VIIIA SMP Negeri 1 Kolaka, taken by using purposive sampling method. This research was carried out in 6 meetings with the subject matter of light and optical instruments. Data collection was conducted by using observation, evaluation, and tests at the end of each teaching cycle; analyze the data through the results of quantitative analysis. The results showed that in the light material, the average score of students' application of physics concepts was 19 out of a total of 30 questions with a high percentage of students belonging to 25.80%, while for optical instruments, the average score of students' physics concept application was 21. from a total of 30 questions with a high percentage of students, 54.8%. Thus, it can be concluded that the provision of environmental-based worksheets can improve the ability of students to apply physics concepts on class VIIIA of SMP Negeri 1 Kolaka.